Investigating the Relationship Between Dance Flow and Improvisation - Yi Gang; Bi Zhang (Art and Society, 2024)
This article explores the intrinsic connection between dance flow and improvisation, aiming to analyze dancers’ thinking and behavioral patterns in dance creation from a psychological perspective. The study points out that the application of flow theory in the field of dance is relatively scarce, while improvisation, as a core skill in dance art, requires dancers to create without preset conditions. The article begins with an overview of flow theory, emphasizing how the flow state facilitates dancers’ technical performance and creativity. It then analyzes the improvisational practices of professional dancers to reveal the positive interactive relationship between flow and improvisation. The research finds that dancers in a flow state are more likely to enter a state of improvisation, and improvisation itself can also stimulate the flow experience. The article concludes with a discussion on the role of dance flow and improvisation in dance education and performance practice, highlighting the importance of relational creativity in dance creation.